The management of body dysmorphic disorder in adolescents: A systematic literature review - Ghosh Tania; Blair Erik (Open Health)
Body dysmorphic disorder (BDD) is a pathological body dissatisfaction characterised by delusional beliefs of a flaw in appearance paired with obsessive-compulsive rituals. This disorder has a high prevalence in adolescence. This study examines the current state of treatment for BDD in adolescents in the UK to establish a baseline of current treatment, and to identify specific areas for further research. A systematic literature review of two databases was carried out and resultant papers were organised using an amended version of the current UK management standards. Six papers met the eligibility criteria and cognitive behavioural therapy was reported as the most effective current treatment. In drawing together the key findings, three areas for further research were highlighted that are of relevance to a broad range of clinicians working in BDD management in adolescence. These included inquiry into mental health professionals’ perspectives, a review of the rate of remission rates, and research into the extent to which schools can influence adolescents’ ideas about body image. The significance of BDD is not reflected in the current literature base. Education of professionals and the wider community is warranted, as is the drive for improved awareness and an increase in the availability of treatment.